Etiologi dan Pencegahan Kasus Iatrogenik pada Perawatan Konservasi Gigi - Winiati Sidharta (Faculty of Dentistry, Universitas Indonesia, 2015)
Although the dental technology procedures has been well developed, errors of treatment in restorative as well as in endodontics are still exist. Diagnosis, case selection, and treatment procedures should be thoroughly executed to evade iatrogenic cases.